When punishment strikes late: the effect of a delay in punishment and punishment feedback on cooperation and efficiency - Waichman, Israel; Stenzel, Lukas (Journal of neuroscience, psychology, and economics, 2019)
Laboratory experiments established that peer punishment is a powerful cooperation-enhancing institution. However, this evidence centers on punishment that affects punishees immediately, whereas in many out-of-lab instances, punishment only takes effect some time after it has been inflicted. Moreover, studying the consequences of a delay in the effect of punishment could shed light on the channels through which punishment facilitates cooperation. A delay may (a) prevent punishees from immediately responding to the punishment and (b) dissolve the perceived link between received punishment and past behavior. In the present study, we model a situation where punishment affects the punishee 5 periods after it has been inflicted. We find that even under a delay in the effect and feedback of punishment, peer punishment is very effective in facilitating cooperation. However, peer punishment is only efficient when a salient link between received punishment and past contributions is established.